Real exchange rate and economic fundamentals : the case of a developing economy - Rasouli, Azam (2004)
Real exchange rate is an important variable in economy's growth. Its fluctuation reflected on the stability of a country's currency .as an important criterion shows the competitiveness of a country in the world. Misalignment of the RER causes disturbance on consumer price index and affects the prices of tradable goods, trade balance and the economic growth. Basically, the real exchange rate can be defined as the nominal exchange rate that takes the inflation differentials among the countries into account. Its importance stems from the fact that it can be used as an indicator of competitiveness in the foreign trade of a country. Because of the important role it plays in an economy as mentioned above, the real exchange rate has been one of the most debated issues both in terms of theory and the practice. This study discusses the existing definitions, calculation methods and interpretations of the real exchange rates. Within this context, the first part of the study will introduce different definitions of the real exchange rates. The calculation methods will be discussed in the second part. Finally, several points that should be taken into account in the interpretation of the real exchange rate movements will be highlighted. The model used in this study is based on the theoretical model developed by Edwards (1989), which is an intertemportal general equilibrium path of the real exchange rate. The ARDL aPJ?roachof cointegration was applied and the empirical analysis of section five shows that the Iranian economy has been subject to variability in the real exchange rate, reflecting the corresponding variability in both domestic (fiscal deficits and inflation) and external (terms of trade) factors.